2011
DOI: 10.1016/j.stem.2011.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Sox2+ Adult Stem and Progenitor Cells Are Important for Tissue Regeneration and Survival of Mice

Abstract: Summary The transcription factor Sox2 maintains the pluripotency of early embryonic cells and regulates the formation of several epithelia during fetal development. Whether Sox2 continues to play a role in adult tissues remains largely unknown. We here show that Sox2 marks adult cells in several epithelial tissues where its expression has not previously been characterized, including the stomach, cervix, anus, testes, lens and multiple glands. Genetic lineage tracing and transplantation experiments demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

34
650
4
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 685 publications
(715 citation statements)
references
References 46 publications
34
650
4
5
Order By: Relevance
“…Apart from its role during early development, Sox2 is also expressed in progenitors at later stages of the mouse embryo (Graham et al, 2003; Doetzlhofer et al, 2006; Klassen et al, 2004; Aubert et al, 2003), and its expression persists in the adult organism in tissue stem cells of stratified and glandular epithelia of ectodermal and endodermal origin, as well as in sensory cells (Merkel and taste bud cells) and spermatogonial stem cells, where it has been proved to be a critical factor sustaining the homeostasis of these tissues (Arnold et al, 2011). Recently also, it has been shown that Sox2 expression diminishes with aging in several tissues in mice and humans (Carrasco‐Garcia et al, 2018).…”
Section: Introduction Results Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Apart from its role during early development, Sox2 is also expressed in progenitors at later stages of the mouse embryo (Graham et al, 2003; Doetzlhofer et al, 2006; Klassen et al, 2004; Aubert et al, 2003), and its expression persists in the adult organism in tissue stem cells of stratified and glandular epithelia of ectodermal and endodermal origin, as well as in sensory cells (Merkel and taste bud cells) and spermatogonial stem cells, where it has been proved to be a critical factor sustaining the homeostasis of these tissues (Arnold et al, 2011). Recently also, it has been shown that Sox2 expression diminishes with aging in several tissues in mice and humans (Carrasco‐Garcia et al, 2018).…”
Section: Introduction Results Discussionmentioning
confidence: 99%
“…In an interesting manner, however, partial depletion of Sox2+ cells causes a reversible disruption of tissue integrity, and restoration of normal tissue homeostasis rescues morbidity. This recovery originates from the action of residual Sox2+ cells capable of reorganizing and regenerating the affected tissues (Arnold et al, 2011). …”
Section: Introduction Results Discussionmentioning
confidence: 99%
See 3 more Smart Citations